PERENCANAAN ANGGARAN PINJAMAN DENGAN PREDIKSI REGRESI LINIER SEDERHANA DAN OPTIMASI MENGGUNAKAN METODE FUZZY TSUKAMOTO - Mustofa, Undang; Yanitasari, Yessy; Dedih, Dedih (ILKOM Jurnal Ilmiah, 2019)
The business world often faces changing conditions in its business activities. The right work plan is needed so that the business world can develop, one of which is budget planning. In planning the loan budget in the Cooperative refers to the limit on the number of submissions, there is no nominal loan budget plan so that the cooperative's cash condition is unstable and can affect the development of the cooperative. Then we need a system that can predict the loan budget needed. The method used in this reserch is simple Linear Regression to predict budgets and Tsukamoto Fuzzy Methods for budget optimization. Predicted the loan budget for April 2019 with a total capital of Rp. 500,000,000 using simple linear regression predictions of Rp. 441,690,000, after optimization using the Tsukamoto Fuzzy Method is Rp. 396,960,000 more savings Rp. 44,730,000 or 10.12%.